2009
DOI: 10.1182/blood-2008-08-175109
|View full text |Cite
|
Sign up to set email alerts
|

EpCAM, a human tumor-associated antigen promotes Th2 development and tumor immune evasion

Abstract: Experimental tumor vaccination and adoptive T-cell therapies show that interferon-␥ (IFN-␥)-producing CD4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 48 publications
6
48
1
1
Order By: Relevance
“…We identified Il4 as a transcriptional target of Hh signaling in T cells, and this is of interest not only because of its pivotal role in Th2 biology, but also because of the function of IL-4 in signaling to other immune cells. Increased IL-4 in tumor microenvironments can inhibit antitumor responses or promote tumor growth (45,46). Of interest, increased IL-4 has been observed in several cancers strongly associated with aberrant Hh signaling (47)(48)(49), and IL-4 derived from tumor-resident T cells sustained growth of follicular B lymphomas (50), tumors known to produce Hh ligands (51).…”
Section: Discussionmentioning
confidence: 99%
“…We identified Il4 as a transcriptional target of Hh signaling in T cells, and this is of interest not only because of its pivotal role in Th2 biology, but also because of the function of IL-4 in signaling to other immune cells. Increased IL-4 in tumor microenvironments can inhibit antitumor responses or promote tumor growth (45,46). Of interest, increased IL-4 has been observed in several cancers strongly associated with aberrant Hh signaling (47)(48)(49), and IL-4 derived from tumor-resident T cells sustained growth of follicular B lymphomas (50), tumors known to produce Hh ligands (51).…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, trAbs recruit and activate different types of immune effector cells at the targeted tumor where they mediate effective tumor cell destruction (3). The interplay between T cells, tumor cells, and accessory cells mainly leads to the induction of a Th1 response, which is a prerequisite for potent tumor rejection (4,5). Furthermore, it has been shown that antigen-presenting cells recruited to the tumor site subsequently present the phagocytosed and processed tumor-associated antigens to T cells (2).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the tumor antigens inducing the T cell response may also play an important part in deciding whether the immune response will promote or inhibit its progression. Ziegler et al in their study on colon cancer demonstrated strong promotion of Th2 type of response by tumor associated antigen EpCAM both invitro and invivo and hence tumor immune evasion [23]. The antigens which may be important for maintenance of CI equilibrium however remain to be identified.…”
Section: What Maintains the CI Equilibrium?mentioning
confidence: 99%